Peta Pemanfaatan Areal Sawit Untuk Pemberdayaan Mantan Kombatan GAM dan Korban Konflik di Aceh Timur - Fadli Jalil (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2015)
This study examines the economic empowerment policies through the commodity of palm oil. This research aims is to investigate the use of the palm plantation forum for the empowerment of former GAM combatants and conflict-affected communities. This study was conducted in East Aceh District, Aceh Province, Indonesia. This study uses qualitative methode. The results showed that the government provided palm plantation in East Aceh district for the empowerment of former GAM combatants and victims of the conflict have embraced 23 of 24 districts. The Location of palm plantation given to former GAM combatants and conflict-affected communities can not be separated each other, even the proposed assistance through the group. Its members consist of three components of the society, ie ordinary people, former GAM combatants and conflict-affected communities. But, in terms of the people of Aceh, actually all the people consider themselves as victims of the bloody conflict under the Soeharto’s New Order.